FAME Storage Time in an Optimized Natural Antioxidant Mixture - Coppo, Rodolfo Lopes; Borsato, Dionísio; Pereira, Jaqueline Laís; da Silva, Hágata Cremasco (Journal of Renewable Energy, 2013)
The study of B100 biodiesel oxidation stability, and its conservation, is extremely important to control its quality, especially regarding storage. Many spices have shown antioxidant effect and are the targets of study. Knowing the oxidation process in greater detail allows a reliable storage period to be stipulated for the biodiesel without its degradation until the time of use. Results have shown that according to the accelerated stove method, the optimal mixture, composed of 100% of oregano extract, can confer a 535-day shelf life to biodiesel without evident oxidation. According to the results obtained by the Rancimat method, the ideal mixture consists of 100% rosemary, resulting in 483 days of storage. The application of the process variable showed that the accelerated stove method was more suitable to determine oxidative stability of biodiesel.